Stylistic features of narrative procedure in a psychological short story in the context of teaching interpretation - Stakić, Mirjana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The paper investigates the stylistic features of narrative procedure in a psychological short story in the context of its interpretation in the teaching of the Serbian language and literature. The narrative procedure in a psychological short story is characterized by the use of the first person in narrating, that is I form, an interior monologue and direct interior monologue, dreams, oversights and introspective. It is also characterized by a particular sentence structure, of often incomplete and elliptical form, used to express the conflicts going on in characters' inner sphere and verbal interaction between the characters. The narrative procedure applied in a psychological short story indicates that its plot is subdued to the internal psychological experiences. During the interpretation of a psychological short story students, through the interpretation of stylistic and narrative procedures, are directed and encouraged to discover complex and often hidden psychological mechanisms which spur the characters to act, influence their behavior, verbal expression and mutual relations. The interpretation of language signs which may have psychological and semantic potential leads to the revealing of unconscious internal psychological processes and mechanisms which take place within a literary character.